Indigenous experience and national positioning: Citizen struggles of Bolivian migrants in the city of La Plata, Argentina - Rodrigo, Federico (2021)
In this article, I propose to analyze the appropriation dynamics of indigenous politicization in Bolivia that occur among Bolivian migrants in La Plata, one of the main cities of the Metropolitan Area of Buenos Aires, Argentina. Based on ethnographic participant observation in the activities of Bolivian migrant associations, consular agencies, Argentine State institu-tions and social and political organizations, my conclusion is that, despite the constraints to adopt ethnic identifications in the political space in the context of reception, migrants explicitly recover forms of identification and collective organization of their country’s indigenous movement. The originality of the article is given by the approach to the relationship between ethniciza-tion and national positioning. Following the previous literature, we note the strengthening of indigenous positions, but these do not appear primarily as a way of presenting and mobilizing demands, but rather as a background of struggle that actively informs their subjectivation as citizens in the destina-tion country. In this respect, indigenous transnational politicization is not constituted in opposition to the parameters of the State; rather, it incorporates an experience that is semanticized as ethnic in the insertion of migrants into the political community.